2021
DOI: 10.1002/acp.3865
|View full text |Cite
|
Sign up to set email alerts
|

Episodic memory contributions to second language lexical development persist at higher proficiencies

Abstract: Summary Individual differences in episodic memory abilities have been linked to second language (L2) lexical development, both theoretically and empirically, but such empirical support has been limited to the earliest phases of word learning. However, the Episodic L2 Hypothesis predicts that L2 lexical representations in more advanced L2 speakers are episodic in nature. To examine whether this means that individual differences in episodic memory also contribute to higher level L2 lexical abilities, we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Another reason may be that the trace retrieval strategy of episodic memory promotes the long-term retention of bilingual vocabulary in the mind. This dovetails with the finding of Zhang et al (2021) that the non-verbal episodic memory ability of highly proficient bilinguals contributes to bilingual vocabulary development. Nonverbal episodic memory skills contribute to lexical competence because participants with them become more proficient at higher levels.…”
Section: Discussionsupporting
confidence: 83%
“…Another reason may be that the trace retrieval strategy of episodic memory promotes the long-term retention of bilingual vocabulary in the mind. This dovetails with the finding of Zhang et al (2021) that the non-verbal episodic memory ability of highly proficient bilinguals contributes to bilingual vocabulary development. Nonverbal episodic memory skills contribute to lexical competence because participants with them become more proficient at higher levels.…”
Section: Discussionsupporting
confidence: 83%
“…Subject-or item-level variability in reliance on these different declarative memory mechanisms may also have added noise to the data, lowering the obtained correlations. If true, this account of our findings would indicate that declarative memory tasks that rely on episodic memory performance to operationalize declarative memory abilities may be tapping distinct, albeit related, declarative mechanisms, adding to noise in the data, and consequently leading researchers to underestimate the actual size of the true relationship between declarative memory abilities and any recently learned language information, assuming the latter would be episodically represented as well, which recent research has shown to be a very likely possibility (e.g., Hamrick et al, 2019;Murphy et al, 2021;Witzel & Forster, 2012;Zhang et al, 2021). However, more research is needed to address this possibility.…”
Section: Discussionmentioning
confidence: 85%
“…We did so by examining whether it was correlated with commonly used nonverbal (Continuous Visual Memory Test: Trahan & Larrabee, 1988) and verbal declarative memory tasks (MLAT-V: Carroll & Sapon, 1959). The Continuous Visual Memory Test (CVMT: Trahan & Larrabee, 1988) has been employed in several studies assessing individual differences in declarative memory and language (e.g., Hamrick et al, 2019;Morgan-Short et al, 2014;Murphy et al, 2021;Ruiz et al, 2018Ruiz et al, , 2021Walker et al, 2020;Zhang et al, 2021). The CVMT examines continuous recognition memory for abstract shapes.…”
Section: Other Declarative Memory Tasksmentioning
confidence: 99%
See 1 more Smart Citation